The linkages between emotional intelligence, perceived organizational support, occupational self-efficacy, and organizational commitment among employees in manufacturing sector - Kunawathy, Selvaraju (2024)
Organizational commitment is a very important aspect in ensuring high productivity and performance among employees. Hence, the main objective of this study was to investigate the relationship between emotional intelligence, perceived organizational support, occupational self-efficacy, and organizational commitment among executives in the manufacturing sector in Klang Valley. The research involved 540 employees, but only 242 out of 260 returned questionnaires were usable for analysis. The data were processed using SPSS version 20 and consist of descriptive statistics, correlation, and regression analysis. The study revealed significant positive relationships between perceived organizational support and organizational commitment, as well as between occupational self-efficacy and organizational commitment. The results infer that perceived organisational support and occupational self-efficacy were the major dominant factors of organisational commitment. The results basically contribute to additional empirical evidence in the field of organizational commitment, perceived organizational support, emotional intelligence, and occupational self-efficacy. In terms of practical implications, the results of the study show that employers should focus on improving organizational support in order to elevate organizational commitment. Additionally, given the significant role of occupational self-efficacy in predicting organizational commitment, it is crucial for employers to nurture occupational self-efficacy among employees or perhaps use this attribute as one of the selection criteria in the staffing process. Furthermore, this research opens doors for similar studies in other sectors such as services, construction, agriculture, and telecommunications.